Work Life Balance Auditor Influenced by Work Family Conflict and Support Supervisor - Azlani Diva Regina; Andi Ina Yustina; Hadi Mahmudah; Christine Novita Dewi (LPPM Universitas Terbuka, 2021)
This research examines whether the role of supervisor support could affect the work-life balance of auditors in public accounting firms, both big four and non-big four. If so, it could be mediated by work-family conflict (work-interfering family and family-interfering work). A web-based survey is used to this research in deploying and delivering the questionnaires to 222 auditors from some public accounting firms listed in Indonesia. The result shows that work-interfere family has been partially mediated the relationship between supervisor support and work-life balance, while family-interfere work has not mediated that relationship. The result also demonstrates that supervisor support negatively correlates and significantly affects work-family conflicts (work-interfere family and family-interfere work). This study suggests creating and developing organizational policies such as family policies that could help supervisors maintain auditor's life. This condition can be attained by minimizing work-family conflict to improve their work-life balance.